1990
DOI: 10.1007/bf01310745
|View full text |Cite
|
Sign up to set email alerts
|

Replicating Marek's disease virus (MDV) serotype 2 DNA with inserted MDV serotype 1 DNA sequences in a Marek's disease lymphoblastoid cell line MSB1-41C

Abstract: We characterized the properties of herpes-type viruses which grew well in a Marek's disease lymphoblastoid cell line, MSB1-41C, inducing cytopathic effect characterized by the formation of syncytial giant cells. Examination of the infectious virus by field inversion gel electrophoresis revealed the presence of DNA of about 180 kbp in both the culture fluid and cell fractions of the infected MSB-41C cells. The DNA was found to consist of Marek's disease virus (MDV) serotype 2 (MDV2) and MDV serotype 1 (MDV1) DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…However, it is possible that certain dissimilarities of MSB-1 cells compared to the T226S and T265L cells might be linked to the observed variation in miR-221/miR-222 expression. These include the co-infection of MSB-1 with BC-1 strain of MDV-1 and HPRS-24 strain of MDV-2 (Hirai et al, 1990;Yao et al, 2007), interference with the p53 pathways due to truncated p53 transcripts (Takagi et al, 2006a, b), differences in the methylation status (Kanamori et al, 1987), and that the RB-1B strain used to transform the other cell lines is more lymphomagenic than BC-1. Also of particular interest was the observed downregulation of p27 Kip1 in all MDV-tumour cell lines despite differential miR-221/miR-222 expression.…”
Section: The Role P27mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that certain dissimilarities of MSB-1 cells compared to the T226S and T265L cells might be linked to the observed variation in miR-221/miR-222 expression. These include the co-infection of MSB-1 with BC-1 strain of MDV-1 and HPRS-24 strain of MDV-2 (Hirai et al, 1990;Yao et al, 2007), interference with the p53 pathways due to truncated p53 transcripts (Takagi et al, 2006a, b), differences in the methylation status (Kanamori et al, 1987), and that the RB-1B strain used to transform the other cell lines is more lymphomagenic than BC-1. Also of particular interest was the observed downregulation of p27 Kip1 in all MDV-tumour cell lines despite differential miR-221/miR-222 expression.…”
Section: The Role P27mentioning
confidence: 99%
“…+ T-cell line derived from a spleen lymphoma induced by the BC-1 strain of MDV-1, (Akiyama & Kato, 1974;Hirai et al, 1990) is capable of inducing tumours when inoculated into susceptible chickens (Doi et al, 1976;Lee et al, 1975). We have recently shown that MSB-1 expresses high levels of MDV-1-and MDV-2-encoded miRNAs Yao et al, 2007Yao et al, , 2008, many of which are expressed at much higher levels than those in infected chicken embryo fibroblasts (CEF) (Burnside et al, 2006;Burnside & Morgan, 2007;Burnside et al, 2008).…”
Section: Msb-1 a Cd4mentioning
confidence: 99%
“…The MSB-1 cell line is derived from a spleen lymphoma induced by a virulent strain of MDV-1 (Akiyama et al 1973). It was previously shown to be coinfected with both MDV-1 (BC-1) and MDV-2 (HPRS24) (Hirai et al 1990). The 54-O cell line was isolated in the TLVI laboratory (INRA, Nouzilly) from an ovary lymphoma induced by recombinant RB1-B virus reconstituted from an infectious genome cloned as a bacterial artificial chromosome (kindly provided by Venugopal Nair).…”
Section: Cell Culture Virus and Treatmentsmentioning
confidence: 99%
“…MSB-1 is an MDV-transformed CD4 ϩ T-cell line derived from a spleen lymphoma induced by the BC-1 strain of MDV-1 (1,30). The MSB-1 cell line, used in this study at passage level 13, has a CD4 ϩ phenotype and has been shown to be coinfected with MDV-1 and MDV-2 (66).…”
mentioning
confidence: 99%